LOCALITY AND THE TRANSFER OF FUNDS IN THE COOPERATIVE BANKING SECTOR IN POLAND - Golec, Maria Magdalena (Copernican Journal of Finance & Accounting, 2018)
One of the most important features of cooperative banks is locality which means concentrating financial activity on a specific area. The consequence of locating the banking activity locally is the use of funds raised from the local market for credit needs of the community. The barrier in this area may be an imbalance between the loans and deposits when the co-operative principle (the local money for local needs) is not met. The paper aims to examine the scope of the principle of locality by the cooperative banks in Poland. The study uses quarterly financial data from the years 2009–2016 the selected group of 75 cooperative banks in Poland. The differentiation of the group of banks is assessed by means of descriptive statistics measurement tools and also in research it is used the econometric regression model. Most cooperative banks are net lenders for money market in Poland. The average value of the loans to deposits ratio is 0.7, and the scope of imbalance deepens in recent years. The reasons for such a situation are the regulations of the cooperative banking sector but also the individual policies of the institutions.